2017
DOI: 10.1007/s10877-017-0023-1
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of oxygen delivery through different oxygen entrainment devices during sedation under low oxygen flow rate: a bench study

Abstract: Sedative anesthetic procedures outside the operating room may depend on cylinders as oxygen source. Cylinders have limited storage capacity and a low oxygen flow rate improves the durability. We conducted the bench study to evaluate the fraction of inspired oxygen (FiO) in different oxygen entrainment devices under low oxygen flow rate. The purpose of the bench study was to provide information to choose appropriate oxygen entrainment devices in non-operating room sedative anesthetic procedures. We utilized a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 18 publications
1
10
0
Order By: Relevance
“…Previous studies indicated that the FiO 2 is affected by the RR, the inspiratory time, the presence of a reservoir from which entrainment occurs, and the presence of an expiratory pause [ 10 , 27 ]. The increase in FiO 2 with increasing oxygen flow rates through an Ncan has been demonstrated in a mannequin model [ 29 , 32 ] and humans [ 7 , 11 , 24 , 35 ]. The study by Gibson et al, which used a nasal cannula for the administration of low-flow oxygen, resulted in only slight increases in tracheal oxygen concentration (23.6% at 3 LPM and 25.4% at 5 LPM).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies indicated that the FiO 2 is affected by the RR, the inspiratory time, the presence of a reservoir from which entrainment occurs, and the presence of an expiratory pause [ 10 , 27 ]. The increase in FiO 2 with increasing oxygen flow rates through an Ncan has been demonstrated in a mannequin model [ 29 , 32 ] and humans [ 7 , 11 , 24 , 35 ]. The study by Gibson et al, which used a nasal cannula for the administration of low-flow oxygen, resulted in only slight increases in tracheal oxygen concentration (23.6% at 3 LPM and 25.4% at 5 LPM).…”
Section: Discussionmentioning
confidence: 99%
“…This experiment included three levels of resistance (R in L/s/cmH 2 O) and compliance (C in mL/cmH 2 O) of TTL to represent the lung mechanics of normal, obstructive, and restrictive lung diseases, as suggested by the manufacturer and previous studies [ 27 , 28 , 29 , 30 ]. In the normal lung model, R5/C60, R20/C80, and R5/C40 were represented as obstructive and restrictive lung diseases, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…This is a simulation study and ethical approval was not required as this study did not involve human subjects. To simulate spontaneous breathing, we prepared a model of spontaneous breathing with reference to the model created by Hsu et al (Figure 1 ) [ 12 ]. A ventilator from an anesthesia apparatus (Fabius Plus; Lübeck, Germany: Draeger, Inc.) and test lungs (Dual adult TTL; Grand Rapids, MI: Michigan Instruments, Inc.) were prepared to reproduce spontaneous respiration.…”
Section: Methodsmentioning
confidence: 99%
“…However, measuring FiO​​​​​​​ 2 in the trachea of the human body is difficult. Some researchers have attempted to simulate FiO​​​​​​​ 2 with a spontaneous respiration model [ 4 , 12 , 13 ]. Thus, in this study, we aimed to measure FiO​​​​​​​ 2 using a simulation model of spontaneous respiration.…”
Section: Introductionmentioning
confidence: 99%
“…2), as suggested by the manufacturer and previous studies. [27][28][29][30] In the normal lung model was R5/C60, R20/C80 and R5/C40 were represented to obstructive and restrictive lung diseases, respectively. The protocols were performed with a wide-ranging change in the ventilatory pattern of the LTV1200 ventilator [V T :300, 500 and 700mL; f:10, 20 and 30breaths/min]; Oxygen flow rates of 1, 3 and 5L/min were set for the nasal cannula.…”
Section: Lung Model and Testing Protocolmentioning
confidence: 99%